Of Tournaments and Temptations: An Analysis of Managerial Incentives in the Mutual Fund Industry - BROWN, KEITH C.; HARLOW, W. V.; STARKS, LAURA T. (Journal of Finance, 1996)
ABSTRACT We test the hypothesis that when their compensation is linked to relative performance, managers of investment portfolios likely to end up as “losers” will manipulate fund risk differently than those managing portfolios likely to be “winners.” An empirical investigation of the performance of 334 growth‐oriented mutual funds during 1976 to 1991 demonstrates that mid‐year losers tend to increase fund volatility in the latter part of an annual assessment period to a greater extent than mid‐year winners. Furthermore, we show that this effect became stronger as industry growth and investor awareness of fund performance increased over time.